THE ROLE OF FORENSIC ANTHROPOLOGISTS: A REVIEW OF THE SITUATION IN BRAZIL (International Seven Journal of Health Research, 2025)
Forensic anthropology has been gaining importance in Brazil, for example, in the context of mass disasters, missing persons, and criminal investigations. One of the cornerstones of the forensic anthropologist's role is identification, and Brazil is no exception. The role of forensic anthropologists has been studied in various locations around the globe, such as Thailand and Australia. In this context, this scientific manuscript aims to analyze the role of forensic anthropologists in Brazil, describing the profession's main roles and clarifying similarities and differences in comparison to other countries. This study is a systematic and integrative literature review, following a pre-established protocol. The PubMed (MEDLINE) and LILACS databases were searched, supplemented by additional research. These searches in PubMed and LILACS yielded an initial number (n) of 104 studies. After removing duplicates, 99 studies were left. After reading titles and abstracts, 85 studies were excluded, leaving 14 articles for full reading. Finally, 13 studies were excluded, leaving 1 article. A complementary search included 5 more relevant studies, resulting in a final "n" of 6. Based on the results, combined with the discussion, it was possible to note that forensic anthropologists in Brazil play essential roles in identifying missing persons, both in criminal and mass disaster contexts. The field is gaining increasing relevance in Brazil, but still faces structural challenges. It is considered that further investment is needed to maintain this growth and overcome the remaining challenges regarding forensic anthropology infrastructure in Brazil. The results of this study should be interpreted in light of its limitations, which include the lack of quality analysis and the lack of paired analysis. There is a need for new systematic reviews on the topic, considering a paired review approach and quality analysis in order to achieve greater scientific rigor and quality in the synthesis of evidence.